Toxocara sero-prevalence and its relationship with allergic asthma in asthmatic patients in north-eastern Iran. Issue 6 (1st October 2018) - Khozime, A.; Mirsadraee, M.; Borji, H.
Abstract: Toxocariasis is an important neglected tropical disease that has been suggested as a possible etiologic agent of asthma. The objective of the present study was to investigate possible significant association between Toxocara seroprevalence and asthma in a clinic-based case-control study. Blood samples were collected from human subjects aged 5–70 years, 50 of whom had signs of asthma and 50 of whom had no signs of asthma. Risk factors for asthma and Toxocara spp. infection were assessed by a questionnaire given to each patient. Blood samples were analysed to measure levels of anti- Toxocara spp. immunoglobulin G (IgG). Patients with bronchial asthma were observed to have higher Toxocara spp. seropositivity than that of the non-asthmatic controls (6 vs 2%, P = 0.47). The mean anti- Toxocara spp. antibody titre was not significantly higher in patients with bronchial asthma than in individuals without asthma ( P = 0.395, 95% CI = 0.579–1.45). There was no significant difference in the mean age, sex, social class, exposure to smoking and presence of domestic dog or cat at home between the two groups ( P ≥ 0.05). The presence of anti- Toxocara spp. IgG was statistically associated with higher blood eosinophils, but it was not associated with asthma ( P ≥ 0.05). The observed relationship between exposure to Toxocara spp. infection and bronchial asthma in Iranian patients warrants further evaluation. An understanding of any potential influence on the pathogenesis of human asthma provides a potential avenue for prevention.